Analisis Fiqhul Bi`ah terhadap Kewenangan Otonomi Daerah dalam Kebijakan Reklamasi Pasca Tambang : Tinjauan Hukum Islam - Hannani, Hannani; Sukri, Indah Fitriani; Hasim, Hasanuddin (DIKTUM: Jurnal Syariah dan Hukum, 2022)
This article aims to describe an overview of Islamic law (fiqhul bi`ah) on post-mining reclamation policies. Mining and mining industries in the area are regulated in the post-mining reclamation policy through Regional Regulations. The coal mining industry has a large-scale environmental impact spread over the regions, especially areas where natural resources thrive. The problem in this research concerns the form of post-mining control in terms of the authority of regional autonomy and how the control and supervision from the government is related to post-mining Reclamation Guarantees, through regional autonomy policies, the emphasis on post-mining reclamation can be controlled with all regional policies. Control in the licensing process does not stop at handling taxes, it is in tune with legal certainty. The research method used in this artilcles is normative juridical by taking data from processed researchers, and using some literature in the form of books, as well as related journal articles. The conclusion in this study, that although the post-mining reclamation process has been actively carried out, the handling efforts have not been maximized, what needs to be done is as an alternative to managing ex-mining land with an environmentally sustainable perspective, encouraging the strengthening of the synergy team in the form of a monitoring team for all stakeholders, the community can participate in prepare the management of ex-mining land and implement the supervisory function.